Spontaneous echo contrast masking thrombus in giant left atrium of mitral stenosis-a dilemma in clinical diagnosis - Islam, A K M Monwarul; Salam, Md. Abdus; Sayeed, Md. Zahidus; Kibria, Md. Golam (2015)
Spontaneous echo contrast (SEC) and thrombus in enlarged left atrium (LA) are common in mitral valvular disease (MVD) and SEC is considered to be a prethrombotic condition. Reliable exclusion of LA thrombus is important before any definitive curative attempts like percutaneous transluminal mitral commissurotomy (PTMC), closed mitral commissurotomy (CMC) or innovative therapies like pulmonary vein isolation and percutaneous closure of the LA appendage. Echocardiography, particularly the transesophageal echocardiography (TEE) is considered to be the gold standard for the diagnosis and to exclude LA thrombus. However, LA thrombus may remain rarely undetected even by TEE potentially making the interventions a risky job. We present a case of mitral stenosis (MS) with giant LA where profuse, dense SEC masked the underlying thrombus in the LA cavity.